Analisis Risiko Kegagalan Menggunakan Metode FMEA pada Mesin Cetak Digital UV di PT XYZ - Tri Wibowo; Novi Purnama Sari; HB Rudi Kusumantoro (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to analyze the failure risks of UV digital printing machines used at PT XYZ using the Failure Mode and Effects Analysis (FMEA) method. In the digital printing industry, the continuity of machine operations heavily depends on effective maintenance to prevent downtime that could disrupt the production process. The FMEA method is employed to identify potential failure modes and evaluate the severity, occurrence, and detection of each failure. This research adopts a quantitative approach, with data collected through observations, interviews, and historical documentation. The analysis reveals that the printhead, cooling system, and UV lamp are the components with the highest Risk Priority Numbers (RPN), at 504, 441, and 288 respectively. Based on these findings, it is recommended that preventive and predictive maintenance strategies be enhanced to avoid recurring failures.